The active participation of children from the municipality of Mosquera, Cundinamarca in online spaces during the pandemic. - Ávila Fuentes, Diana Marcela; Díaz Torres, Jessica; Fajardo Pinzón, Valentina (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of the research was focused on promoting the active participation of children between the ages of 4 and 12 in the municipality of Mosquera-Cundinamarca, Colombia through online spaces, thus making the voices of the group selected for this process visible. This experience occurred in times of pandemic, thus preventing face-to-face meetings, resolving the need to open up virtuality, and through it a series of workshops were generated that arose from the interests of these childhoods, thus allowing to strengthen the leadership skills, collaborative work, cooperative. This study is carried out from qualitative research with a hermeneutic approach where the following tools were used: interviews, surveys, observation, and the pedagogical documentation of the different workshops and the minutes of the meetings of the reflection spaces.